Cover Image. Issue 2 (9th April 2021) - Unknown
Abstract : The rigidity of an injection‐molded isotactic polypropylene (PP) containing 1, 3:2, 4‐bis‐o‐(4‐methylbenzylidene)‐D‐sorbitol (MDBS) as a crystal nucleating agent can be enhanced by the selection of appropriate processing conditions. Transmission electron microscopy observation reveals that MDBS fibrils strongly align to the flow direction under the low‐temperature processing, as shown at the bottom of the cover image from Masayuki Yamaguchi and colleagues. In contrast, with high‐temperature processing beyond its dissolution temperature and in conventional conditions, the modulus decreases due to no orientation of MDBS fibers (shown in the top portion of the image). (doi.org/10.1002/pcr2.10170 ) Abstract : The rigidity of an injection‐molded isotactic polypropylene (PP) containing 1, 3:2, 4‐bis‐o‐(4‐methylbenzylidene)‐D‐sorbitol (MDBS) as a crystal nucleating agent can be enhanced by the selection of appropriate processing conditions. Transmission electron microscopy observation reveals that MDBS fibrils strongly align to the flow direction under the low‐temperature processing, as shown at the bottom of the cover image from Masayuki Yamaguchi and colleagues. In contrast, with high‐temperature processing beyond its dissolution temperature and in conventional conditions, the modulus decreases due to no orientation of MDBS fibers (shown in the top portion of the image). (doi.org/10.1002/pcr2.10170 )